Il Certamen Homeri et Hesiodi fra Alcidamante e la tradizione biograﬁca omerica e l’origine della Vita Ps.-Erodotea - Lucarini, Carlo M. (Hyperboreus, 2019)
This paper investigates the relationship between the Certamen Homeri et Hesiodi, Alcidamas and the Homeric biographical tradition. The Certamen is preserved in a late abridgment (Certamen Laurentianum), which derives from an Urcertamen and a lost Homeric biography. The Urcertamen was favourable to Hesiod, and I believe that Plutarch (Sept. sap. conv. 153 F) depends on it. The Karanis-Papyrus has shown rather paradoxically that F. Nietzsche was right in assuming that the rhetor Alcidamas played an important role in the creation of our Certamen, and I suggest that it was Alcidamas who ﬁrst combined the Urcertamen and the lost Homeric biography, giving the new work a pro-Homeric tendency. It is possible that Alcidamas’ praise of Homer was provoked by Plato’s attack on poetry. The Vita Herodotea (which I date to the second century AD) polemizes against the biographical source used by the Certamen; its author adopts a Herodotean attitude towards the Colophonians. A new critical edition of the Karanis-papyrus and a detailed Quellenanalyse of the Certamen Laurentianum are also provided.